Investigation of The Trend of Agricultural Land Use Changes in the Zayandeh Rood Watershed Using Google Earth Engine Platform - Pantea Lotfi; Mozhgan Ahmadi Nadoushan (محیط زیست و توسعه فرابخشی, 2024)
Introduction: Drought is a natural phenomenon that occurs almost in most regions of the world, and due to its relationship with agricultural products and water resources, it is considered as one of the most important issues in environmental sciences. The effects of this phenomenon are greater in arid and semi-arid regions due to their less annual rainfall. In contrast to traditional methods, the use of remote sensing techniques and satellite images has been considered as a useful tool for agricultural drought monitoring. The main objective of this study is to investigate changes in agricultural land use using normalized vegetation difference index and satellite images.Materials and Methods: In this study, Landsat satellite images were used to investigate the trend of agricultural land use changes in the Zayandeh Rood catchment during 1984-2023. To do this study, the normalized plant difference index was used for each year. Since various patterns of cultivation with different time differences are present in the study area during a year, it is not possible to use a selected image as the basis of a year, on the contrary, it is necessary to examine different images for different times of the year. To identify and specify the set of all the pixels that have gone under the cultivation surface in one crop year. Since this process would be very time-consuming, an innovative approach was used. First, in the Google Earth Engine system, all the annual Landsat images were called year by year. Then, the images with cloud cover were removed and the maximum filter was applied to the bands of the remaining images. Then, the normalized vegetation difference index of new annual images was created and by applying a threshold of 0.2, agricultural lands were separated from other lands. The extent of agricultural land was calculated in each year and the linear regression model was used to identify the change process. In other words, the extent of agricultural land was used as a dependent variable and time was used as an independent parameter on an annual scale.Results: The extent of agricultural land in 1984 was about 25 thousand hectares, which with a decreasing trend over time reached 21700 and 15180 hectares in 1994 and 2014, and finally reached its lowest value in 1401. It has reached 11.250 hectares. This trend shows a 55% reduction in the abandonment of agricultural land at this point in time. Also, the value of the normalized plant difference index in agricultural lands has experienced a decreasing trend over time, which indicates the change in the cultivation pattern towards low-density crops with low biomass such as wheat.Discussion: The results of the changes in the extent of agricultural use in the study area showed a decreasing pattern, so, there has been a loss of agricultural land, which is consistent with the decreasing pattern of the water level of the Zayandeh Rood watershed. This phenomenon can be directly attributed to the reduction of water resources in the region. In the last decade, the amount of water allocated to carry out agricultural activities in this region has decreased a lot due to the water volume of the Zayandeh Rood watershed approaching critical limits.